Fibroblastic reticular cells enhance T cell metabolism and survival via epigenetic remodeling - Brown, Flavian D.; Sen, Debattama R.; LaFleur, Martin W.; Godec, Jernej; Lukacs-Kornek, Veronika; Schildberg, Frank A.; Kim, Hye-Jung; Yates, Kathleen B.; Ricoult, Stéphane J. H.; Bi, Kevin; Trombley, Justin D.; Kapoor, Varun N.; et al. (Nature immunology, 2019)
Lymph node fibroblastic reticular cells (FRCs) respond to signals from activated T cells by releasing nitric oxide, which inhibits T cell proliferation and restricts the size of the expanding T cell pool. Whether interactions with FRCs also support the function or differentiation of activated CD8 + T cells is not known. Here we report that encounters with FRCs enhanced cytokine production and remodeled chromatin accessibility in newly activated CD8 + T cells via interleukin-6. These epigenetic changes facilitated metabolic reprogramming and amplified the activity of pro-survival pathways through differential transcription factor activity. Accordingly, FRC conditioning significantly enhanced the persistence of virus-specific CD8 + T cells in vivo and augmented their differentiation into tissue-resident memory T cells. Our study demonstrates that FRCs play a role beyond restricting T cell expansion—they can also shape the fate and function of CD8 + T cells. Fibroblastic reticular cells (FRCs) are dynamic regulators of lymphoid tissue structure. Turley and colleagues show FRCs also support activated T cells by producing IL-6, which confers an advantage to CD8+ T cell memory responses.